The Use of Historical Novel in Social Studies Course and Its Effect on Creative Writing Skills of Students - Dolmaz, Mustafa; Kaya, Erol (Journal of History Culture and Art Research, 2018)
In this study, the effect of the use of historical novels with different forms of fiction on the creative writing skills of the students in social studies course was studied. The study group consists of 80 students from 4 different classes in the 7th grade of a state school in Sivas province. The study group consists of 3 experimental and 1 control group, each of which consists of 20 people. The research was carried out in the pretest-posttest control group experiment design. In addition, while examining the creative writing activities of the students, document analysis and creative writing rubrics developed by Öztürk (2007) were used. After determining the homogeneity of variance and the normality of data distribution, one-way variance analysis, anova analysis in repeated measurements and Tukey test analysis were performed on the data obtained from the creative writing studies of the students. In addition, the arithmetic mean of creative writing studies was also used. In each experimental group, in addition to the curriculum, historical novels with different fiction forms (classical, modern and postmodern) were used. In the control group, the course was continued in line with the curriculum. As a result of the research, postmodern and modern fiction-style historical novels have been observed to be very effective on the creative writing skills of the students. Classical historical novels based on chronology, on the other hand, have been determined to have little effect on the creative writing skills of the students.